2005
DOI: 10.1002/cvde.200404201
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Study of the Growth and Resistivity of Nanocrystalline Pt Films Obtained from Pt(acac)2 in the Presence of Oxygen or Water Vapor

Abstract: d Mass production of millimeter long SWNTs with a very high production yield of SWNTs to catalyst.d Ease of up-scaling by introducing an antenna array (i.e., multiple antennae) for mass production of SWNTs on very large, flat substrates. Unlike other MPCVD, it is unnecessary to consider the geometric and electric boundary conditions. In conclusion, our point-arc MPCVD method is preferable for controlled growth of SWNTs at a low (600 C) temperature on Si substrates coated with a sandwich-like coating structure;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…A possible explanation could be the smaller particle size on initial stages, as observed in Ir depositions at lower deposition temperatures. Data obtained by Prof. Battiston and his colleagues [11] have confirmed our observations that decreasing deposition temperature results in Pt coatings with a more compact (111) structure. A third observation was the effect of precursor concentration.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A possible explanation could be the smaller particle size on initial stages, as observed in Ir depositions at lower deposition temperatures. Data obtained by Prof. Battiston and his colleagues [11] have confirmed our observations that decreasing deposition temperature results in Pt coatings with a more compact (111) structure. A third observation was the effect of precursor concentration.…”
Section: Discussionsupporting
confidence: 87%
“…The effects of decarburizing species like oxygen and water vapor were also confirmed in one of the last works of Prof. Battiston. [11] It was also observed that decreasing the deposition temperature leads to lower crystal sizes and more compact structures. A possible explanation could be the smaller particle size on initial stages, as observed in Ir depositions at lower deposition temperatures.…”
Section: Discussionmentioning
confidence: 94%
“…[39] In both cases, the surface reaction rates rose exponentially with temperature, suggesting a kinetic-controlled domain; the apparent activation energy was 110 and 91 kJ mol -1 in the presence of oxygen and water vapor, respectively. However, the films obtained with oxygen suffered from spatial non-homogeneity that caused a restriction in the useful temperature interval to 240-260°C, while at higher temperatures the films grew only in the first few centimeters of the reactor.…”
Section: Pt Filmsmentioning
confidence: 98%
“…[ 39] On the basis of all the above observations, the platinum films utilized for further investigations were deposited at 380°C in the presence of water vapor. Moreover, in order to establish the minimum film thickness (and, in principle, low cost) that allowed good electrochemical properties to be achieved, Pt films with thicknesses over the range 10 to 200 nm were studied.…”
Section: Pt Filmsmentioning
confidence: 99%
“…Suitable MOCVD precursors are required to be volatile, thermally stable at vaporization, nontoxic, stable in air and easy to prepare in high yields . Pt forms volatile compounds with methyl, allyl, cyclopentadienyl (Cp) and β‐diketonato ligands . These types of Pt precursors were usually used for a definite purpose.…”
Section: Introductionmentioning
confidence: 99%